Writing literary history in the Greek and Roman world - Fedeli, Giacomo; Spelman, Henry 1987- (Cambridge University Press, 2024)
"Covering a wide variety of Greek and Latin texts spanning from the Archaic period down to Late Antiquity, this volume represents the first concerted attempt to understand ancient literary history in its full complexity and on its own terms, thereby provoking reflection on writing the history of ancient literature today."
Literaturverzeichnis Seite 343-379
Keywords: Griechisch; Literaturgeschichtsschreibung; Latein; Classical literature / History and criticism; Literary criticism; Aufsatzsammlung